Analisis Desain Kelembagaan Pengelolaan Program Bus Sekolah di Kota Surabaya - Fadlur Rohman, Ahmad Zaki; Wiwoho, Theofilus Maharedi Aristyo (International Journal of Demos (IJD), 2023)
AbstractThis research begins with an institutional study that wants to formulate an adapted design within the framework of an institution or institutions. This research attempts to explore the institutional design contained in the management of the Surabaya School Bus by looking at the institutional design contained in the Surabaya School Bus management program. These activities include routine pick-up and delivery activities for Surabaya City students every day along with additional activities such as incidental activities outside of routine activities. The existence of these activities is influenced by external variables which include Physical/Material Conditions, Community Attributes, and the Rules used. This study uses a qualitative research approach with the type of research adopted is a case study. While the theory used is the theory of IAD (Institutional Analysis Development) by Elinor Ostrom. The results found in this study indicate that the institutional design contained in the management of the Surabaya School Bus through external variables of physical/material conditions is known if the availability of route options and School Bus units has not been able to reach the entire city of Surabaya. Meanwhile, based on the community attribute variables reviewed through the management side, there is a loss in the number of actors with the workload handled. Then for the rule variable used it is known if the Surabaya School Bus does not yet have city-level regulatory rules regulated through a mayoral regulation. There are also several instructions that are inefficient in their implementation, such as regulations for repairs and limited land for refueling.Keywords: Institutional Design, Institutional Analysis and Development (IAD), Surabaya School BusÂ AbstrakPenelitian ini berawal dari studi kelembagaan yang ingin memformulasikan desain yang diadopsi dalam kerangka kerja suatu institusi atau kelembagaan. Penelitian ini mencoba untuk menelusuri desain kelembagaan yang terdapat dalam pengelolaan Bus Sekolah Surabaya dengan melihat desain kelembagaan yang terdapat pengelolaan program dari Bus Sekolah Surabaya dapat dilihat dari aksi situasi yang terjadi pada saat aktivitas kegiatan Bus Sekolah Surabaya berjalan di Kota Surabaya. Aktivitas tersebut meliputi kegiatan giat rutin pengantaran maupun penjemputan siswa-siswi pelajar Kota Surabaya setiap harinya beserta kegiata-kegiatan tambahan seperti giat isidentil diluar dari giat rutin. Adanya kegiatan tersebut dipengaruhi oleh variabel eksternal yang meliputi atas Kondisi Fisik/Material, Atribut Komunitas, dan Aturan yang digunakan. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan jenis penelitian yang diadopsi ialah studi kasus. Sedangkan teori yang digunakan ialah teori IAD (Institusional Analysis Developmnet) oleh Elinor Ostrom. Adapun hasil yang ditemukan dalam penelitian ini menunjukan bahwasannya desain kelembagaan yang terdapat dalam pengelolaan Bus Sekolah Surabaya melalui variabel eksternal kondisi fisik/material diketahui jika ketersediaan pilihan rute dan unit Bus Sekolah belum mampu menjangkau keseluruhan Kota Surabaya. Adapun berdasarkan variabel atribut komunitas yang ditinjau melalui sisi pengelola, terdapat ketidakseimbangan jumlah aktor dengan beban kerja yang ditangani. Kemudian untuk variabel aturan yang digunakan diketahui jika Bus Sekolah Surabaya belum memiliki aturan regulasi tingkat kota yang diatur melalui peraturan walikota. Terdapat juga beberapa instruksi yang tidak efisien dalam penerapannya seperti regulasi untuk perbaikan dan terbatasnya lokasi untuk pengisian BBM.Kata Kunci: Desain Kelembagaan, Institutional Analysis and Development (IAD), Bus Sekolah Surabaya